Turkish-Islamic type management scale through the Nizamülmülk ideas - Şen, Alper Tunga; Savi, Fatma Zehra (Afyon Kocatepe Üniversitesi)
Management science has emerged as a field that has attracted much attention, and different management models are constantly being researched. As a result, scientists are frequently on the agenda and conducting in-depth studies to develop a better or more ideal management model. The primary purpose of this study is to create a valid and trustworthy seven-dimensional scale to introduce a new management model to the literature. The scale has a unique value in that it fully covers the seven sub-dimensions it takes and is performed for the first time. Consequently, a valid and reliable scale was developed based on Siyasetname, one of Nizamülmülk's works. After the analysis, it was confirmed that it was an appropriate descriptive scale consisting of 32 items and seven sub-dimensions. The goodness-of-fit values of the scale (CMIN/SD: 2.13, RMSEA: 0.065, CFI: 0.93, GFI: 0.82, NFI: 0.89, SRMR: 0.067) were within acceptable ranges. This scale creates an opportunity to compare the management models preferred today, which is important for determining suitable management models. The article ends with a discussion of the theoretical and practical results and suggestions for future research.

Yönetim bilimi, oldukça ilgi gören ve farklı yönetim modellerinin sürekli araştırıldığı bir alan olarak ortaya çıkmıştır. Sonuç olarak bilim insanları daha iyi veya daha ideal bir yönetim modeli geliştirmek için sıklıkla konuyu gündeme getirmekte ve birçok derinlemesine çalışma yürütmektedirler. Bu makalenin temel amacı, literatüre yeni bir yönetim modeli kazandırmak adına geçerli ve güvenilir yedi boyutlu bir ölçek oluşturmaktır. Ölçek, içerdiği yedi farklı alt boyutu tam olarak kapsaması ve ilk kez uygulanması açısından benzersiz bir değere sahiptir. Yapılan çalışma neticesinde Nizamülmülk’ün eserlerinden biri olan Siyasetname’den yola çıkılarak geçerli ve güvenilir bir ölçek geliştirilmiştir. Yapılan analiz sonrasında 32 madde ve yedi alt boyuttan oluşan, uygun ve açıklayıcı bir ölçek olduğu doğrulanmıştır. Ölçeğin uyum iyiliği değerlerinin (CMIN/SD: 2,13, RMSEA: 0,065, CFI: 0,93, GFI: 0,82, NFI: 0,89, SRMR: 0,067) kabul edilebilir aralıklarda olduğu görülmektedir. Oluşturulan bu ölçek ile günümüzde tercih edilen yönetim modellerinin karşılaştırılmasına imkân vererek, kendilerine uygun yönetim modellerini belirleyebilmeleri konusunda önem teşkil etmektedir. Makale, teorik ve pratik sonuçların tartışılması ve gelecekteki araştırmalar için önerilerde bulunulmasıyla sona ermektedir.
Nizamülmülk fikirleri ışığında Türk-İslam tipi yönetim modeli ölçeği
Keywords: Management; Management Model; Nizamülmülk; Siyasetname; Yönetim; Yönetim Modeli